2004
DOI: 10.1007/s00705-004-0390-z
|View full text |Cite
|
Sign up to set email alerts
|

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China

Abstract: Degenerate primers were used to detect and amplify 3'-terminal genome fragments of potyviruses from medicinal aroid plants growing at 16 sites in China. Virus was detected in 7 samples of which six, all of Pinellia ternata, contained a strain of soybean mosaic virus (SMV) similar to that previously reported from this host in China. The complete sequence of one isolate and the P1 protein coding region of the other isolates were also sequenced. In all cases, the P1 proteins resembled isolates of Dasheen mosaic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…ex Breitenb. in China (Chen et al ., 2004) and was later found to occur widely in aroid plants (Shi et al ., 2005). This strain could be mechanically inoculated to some soybean cultivars, in which it induced weak symptoms.…”
Section: Introductionsupporting
confidence: 91%
“…ex Breitenb. in China (Chen et al ., 2004) and was later found to occur widely in aroid plants (Shi et al ., 2005). This strain could be mechanically inoculated to some soybean cultivars, in which it induced weak symptoms.…”
Section: Introductionsupporting
confidence: 91%
“…KoMV belongs to the family Potyviridae , and infects aroids, including Amorphophallus , Caladium , Colocasia , Dieffenbachia , Philodendron , Typhonium , Zamioculcas and Zantedeschia species (Alexandre, Duarte, Rivas, Kitajima, & Harakava, 2013; Chang, Chen, & Chung, 2001; Manikonda et al, 2011; Padmavathi, Srinivas, Hema, & Sreenivasulu, 2013; Shi et al, 2005; Shimoyama, Kameya‐Iwkai, Hanada, & Gunji, 1992). KoMV‐infected calla lilies show symptoms such as mosaic, green islands, veinal chlorosis on leaves, leaf distortion, short peduncles and discoloured pigmented flecks on the spathes (Chang et al, 2001; Pham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…KoMV infection causes yield losses and decreases the value of the commodity. KoMV has been spread worldwide, including to Brazil, China, Germany, India, Japan, Korea, Taiwan, the Netherlands and New Zealand (Alexandre et al, 2013; Chang et al, 2001; Kwon, Ha, Yoon, & Ryu, 2002; Lesemann & Winter, 2002; Manikonda et al, 2011; Pham et al, 2002; Shi et al, 2005; Shimoyama et al, 1992; Wei, Pearson, Cohen, Tang, & Clover, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The genome is 9,544 nucleotides long excluding the 3-terminal polyA tail and encodes a typical potyviral 350 kDa polyprotein of 3,087 amino acids [16]. Some researchers had found that ZaMV could infect calla lily plants in Taiwan, Korea, and Typhomium flagelliforme in China [16][17][18]. Okuno et al [19] had isolated JHMV from Japanese hornwort plants (Cryptotaenia japonica) with mosaic disease symptoms.…”
Section: Introductionmentioning
confidence: 99%